2004
DOI: 10.1177/0743558403260019
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Religiosity on Adolescent Sexual Behavior:

Abstract: Longitudinal studies published between 1980 and 2001 (N = 10) are reviewed for evidence that the religiosity of adolescents is causally related to their sexual behaviors. Results indicate that religiosity delays the sexual debut of adolescent females. Findings are mixed for adolescent males. Although only half of the studies examined the effects of race and ethnicity, results of these studies reported similar effects for White and Black adolescents. These findings are discussed in light of their implications f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
214
3
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(246 citation statements)
references
References 27 publications
(58 reference statements)
22
214
3
7
Order By: Relevance
“…"Without correctly specifying the causal influence in both directions, empirical estimates of the impact of religion on adolescent sexuality will be biased" (Thornton and Camburn, 1989). Nevertheless, often the two processes are in fact separately analysed, or cross-sectional data are used that do not allow separation of the reciprocal effect (Rostosky et al, 2004). "There are very few studies that have explored possible reciprocal relationships between religiosity and first sex" (Meier, 2003).…”
Section: Hypotheses and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…"Without correctly specifying the causal influence in both directions, empirical estimates of the impact of religion on adolescent sexuality will be biased" (Thornton and Camburn, 1989). Nevertheless, often the two processes are in fact separately analysed, or cross-sectional data are used that do not allow separation of the reciprocal effect (Rostosky et al, 2004). "There are very few studies that have explored possible reciprocal relationships between religiosity and first sex" (Meier, 2003).…”
Section: Hypotheses and Methodologymentioning
confidence: 99%
“…Many scholars suggest that, together with the effect of religion on sexual behaviour, there may also be a reciprocal influence between sexual behaviour and religiosity (Thornton and Camburn, 1989;Benda and Corwyn, 1997;Rostosky et al, 2004). However, results in this direction are controversial and, in particular, are not statistically significant for young Americans (Meier, 2003;Hardy and Raffaelli, 2003).…”
Section: Hypotheses and Methodologymentioning
confidence: 99%
“…Broadly, religiosity may be defined as a set of institutionalized beliefs, doctrines and rituals, and ethical standards for how to live a good life (Holder et al 2000). Most research supported that adolescents who were more religious tended to delay sexual activity (Kirby 2002;Rostosky et al 2004). For male and female teens, frequent attendance at religious services and religious youth activities, higher levels of importance of religion in daily life and religious feelings, and increased adherence to religious teachings were all significantly related to decreased rates of voluntary sexual debut (Fehring et al 1998;Holder et al 2000;Lammers et al 2000;Lefkowitz et al 2004;McCree et al 2003;Nonnemaker et al 2003;Rostosky et al 2003).…”
Section: Religiositymentioning
confidence: 99%
“…Moreover, studies of representative samples of U.S. youths show that White, African American, Hispanic, and Asian American adolescents who are religious (measured as frequency of church attendance and self-rated importance of religion) wait longer before first intercourse (Regnerus, 2007;Rotosky, Regnerus, & Wright, 2003), have lower rates of having ever given or received oral sex (Regnerus, 2007), and have lower rates of ever having been pregnant (Nonnemaker, McNeely, & Blum, 2003). Recent systematic and meta-analytic reviews (Lucero, Kusner, Speace, & O'Brien, 2008;Rotosky, Wilcox, Comer Wright, & Randall, 2004) concur with these conclusions.Religious youths also tend to have higher grade point averages and standardized test scores than do their less religious counterparts (Regnerus, 2000;Regnerus & Elder, 2003). Indeed, a metaanalysis of 15 studies on the association of religiousness and school achievement in Black and Hispanic American youths (Jeynes, 2002) found that religiousness was positively associated with grade point average (mean r ϭ .21) and achievement test scores (mean r ϭ .15).…”
mentioning
confidence: 99%